Nuclear and chloroplast genome variability in leek (Allium porrum L.) - E. A. Dyachenko; T. M. Seredin; M. A. Filyushin (Вавиловский журнал генетики и селекции)
The genus Allium L. (Amaryllidaceae), the most numerous among monocotyledonous plants, includes such economically important vegetable crops as onion (A. cepa), garlic (A. sativum) and leek (A. porrum). Leek has a high taste and proven valuable dietary properties and is one of the most popular vegetable crops in Western Europe. Despite a high importance of leek as a vegetable, this species is rarely the subject of molecular genetic studies. The genetic diversity of leeks has never been studied before. Therefore, in this work, we studied the nuclear variability (AFLP) and the chloroplast (nucleotide sequence analysis) genomes using a broad sample. For this work, 65 leek accessions were selected from the collection of the Scientific Center of Vegetable Crops, which included varieties of domestic and foreign breeding. As a result of an AFLP analysis and processing of the DNA spectra obtained, 760 fragments were identified, of which 716 were polymorphic for the leek accessions being analyzed. The calculated genetic distances between the leek samples varied from 0.4 to 0.76, which is comparable to the intraspecific polymorphism of related Allium species (onions, garlic). Analysis of the genomic structure with STRUCTURE 2.3.4 divided the leek samples into seven groups, which generally coincides with the clustering of these samples. To assess the variability of the chloroplast genome, nine sites of the chloroplast genome were sequenced in the leek samples, both non-coding (intergenic spacers rpl32-trnL, ndhJ-trnL, and intron rps16 gene), and protein coding genes (psaA, psaB, psbA, psbB, psbE, petB). The analysis of the sites of the leek chloroplast genome revealed an extremely low level of their polymorphism, only six SNPs were detected in the studied sequences with a total length of about 10,500 bp. Thus, as a result of this work, a high level of polymorphism of the leek nuclear genome was revealed, while the polymorphism of the chloroplast genome was extremely low.